2022
DOI: 10.3389/fmicb.2022.1024441
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing microalgal lipid accumulation for biofuel production

Abstract: Microalgae have high lipid accumulation capacity, high growth rate and high photosynthetic efficiency which are considered as one of the most promising alternative sustainable feedstocks for producing lipid-based biofuels. However, commercialization feasibility of microalgal biofuel production is still conditioned to the high production cost. Enhancement of lipid accumulation in microalgae play a significant role in boosting the economics of biofuel production based on microalgal lipid. The major challenge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Lipid-rich microalgal strain is a prerequisite for bio-jet production in the HEFA process. However, the production of lipid-rich microalgal biomass is counterproductive [217], and extracting the lipid from the harvested biomass is energy-intensive [218]. Unless other value-added metabolites could be marketed in large volume, the application of the HEFA process would be limiting.…”
Section: Microalgal Biojet Fuelmentioning
confidence: 99%
“…Lipid-rich microalgal strain is a prerequisite for bio-jet production in the HEFA process. However, the production of lipid-rich microalgal biomass is counterproductive [217], and extracting the lipid from the harvested biomass is energy-intensive [218]. Unless other value-added metabolites could be marketed in large volume, the application of the HEFA process would be limiting.…”
Section: Microalgal Biojet Fuelmentioning
confidence: 99%
“…Production of Diesel by microalgae strain is restricted to the laboratory experimental and pilot scale production as a result of costs associated with downstream and upstream production processes (Ambaye et al, 2021;Mahapatra et al, 2021;Mathimani & Mallick, 2018). Despite this challenges, a lots of strategies have been developed and adopted in a bid to reduce the cost of diesel production from microalgae isolates, discussions that have been entirely removed from the present findings that mainly targets usefulness and content of diesel obtained from microalgae, processes insights and factors during production process that hinder the yield and proper harvesting and methods of extraction (Ananthi et al, 2021;Zhu et al, 2022).…”
Section: Highlightsmentioning
confidence: 99%
“…Additionally, up-regulation of KAS-I has been found to significantly enhance lipid synthesis. It has been suggested that the coordinated regulation of multiple genes involved in lipid synthesis may be more effective than targeting a single gene [239]. Overall, abiotic stress induction and gene regulation are feasible approaches to promote lipid synthesis…”
Section: Abiotic Stress Induced Genes Responsible For Lipid Productionmentioning
confidence: 99%